2015
DOI: 10.1038/hortres.2015.59
|View full text |Cite
|
Sign up to set email alerts
|

A basic helix-loop-helix transcription factor, PhFBH4, regulates flower senescence by modulating ethylene biosynthesis pathway in petunia

Abstract: The basic helix-loop-helix (bHLH) transcription factors (TFs) play important roles in regulating multiple biological processes in plants. However, there are few reports about the function of bHLHs in flower senescence. In this study, a bHLH TF, PhFBH4, was found to be dramatically upregulated during flower senescence. Transcription of PhFBH4 is induced by plant hormones and abiotic stress treatments. Silencing of PhFBH4 using virus-induced gene silencing or an antisense approach extended flower longevity, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 54 publications
0
55
0
Order By: Relevance
“…Thus, RhHB1 mediates the antagonistic effect of GAs on ABA and ethylene during rose petal senescence, and the induction of petal senescence by ABA or ethylene operates through a RhHB1-RhGA20ox1 regulatory checkpoint. Another recent study suggests that a reduction in the bioactive GA content enhances the ethylene-mediated flower senescence (Yin et al, 2015). In this study, the overexpression of a basic helix-loop-helix ( bHLH ) transcription factor, PhFBH4 , increased the abundance of transcripts of ethylene biosynthesis genes and also increased ethylene production.…”
Section: Flower Senescencementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, RhHB1 mediates the antagonistic effect of GAs on ABA and ethylene during rose petal senescence, and the induction of petal senescence by ABA or ethylene operates through a RhHB1-RhGA20ox1 regulatory checkpoint. Another recent study suggests that a reduction in the bioactive GA content enhances the ethylene-mediated flower senescence (Yin et al, 2015). In this study, the overexpression of a basic helix-loop-helix ( bHLH ) transcription factor, PhFBH4 , increased the abundance of transcripts of ethylene biosynthesis genes and also increased ethylene production.…”
Section: Flower Senescencementioning
confidence: 99%
“…In this study, the overexpression of a basic helix-loop-helix ( bHLH ) transcription factor, PhFBH4 , increased the abundance of transcripts of ethylene biosynthesis genes and also increased ethylene production. Moreover, the increased expression of the GA metabolic gene GA2ox3 in PhFBH4-OX transgenic plants would raise bioactive GAs content, while silencing PhFBH4 would reduce their levels (Yin et al, 2015). Another study reported that the transcriptome changes associated with delayed flower senescence on transgenic petunia by inducing the expression of etr1-1 , down-regulated genes involved in gibberellin biosynthesis, response to gibberellins stimulus, and ethylene biosynthesis, at different time points (Wang H. et al, 2013).…”
Section: Flower Senescencementioning
confidence: 99%
“…bHLH TFs have been identified as key regulators in controlling anthocyanin biosynthesis in various plant species (Jaakola, 2013). In addition to their function in mediating pigment formation, some of these bHLH TFs can also influence ethylene biosynthesis by activating the expression of ACO or ACS genes (Yin et al, 2015;Li et al, 2017;Alessio et al, 2018), suggesting their vital roles in the regulation of ethylene biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…These include ETHYLENE INSENSITIVE3 (EIN3)-like genes in carnation ( Dianthus caryophyllus ; Iordachescu and Verlinden, 2005) and ETHYLENE-RESPONSIVE ELEMENT BINDING FACTORS (ERFs) in daffodils (Hunter et al , 2002) and petunia ( Petunia hybrida ; Liu et al , 2010). More recently, virus-induced gene silencing and overexpression studies have revealed a basic helix-loop-helix transcription factor, PhFBH4, that positively controls the timing of petunia flower senescence, likely by regulating induction of the ethylene biosynthetic pathway (Yin et al , 2015). …”
Section: Introductionmentioning
confidence: 99%